Respuesta :
Answer:
[tex]f(x)=(x-2)(x)(x+4)^2[/tex]
Step-by-step explanation:
Since there is a multiplicity at x=-4, that would meant that that part of the factor would have to have an even degree. This means that it would have to be 2.
This would give you [tex]f(x)=(x-2)(x)(x+4)^2[/tex]
Answer:
[tex]f (x) = x (x + 4)^2(x-2)[/tex]
Step-by-step explanation:
The zeros of the polynomial are all the values of x for which the function [tex]f (x) = 0[/tex]
In this case we know that the zeros are:
[tex]x = -4,\ x+4 =0[/tex]
[tex]x = -4,\ x+4 =0[/tex]
[tex]x = 0[/tex]
[tex]x = 2[/tex], [tex]x - 2 = 0[/tex]
Now we can write the polynomial as a product of its factors
[tex]f (x) = x (x + 4)(x+4) (x-2)[/tex]
[tex]f (x) = x (x + 4)^2(x-2)[/tex]
Note that the polynomial is of degree 4 because the greatest exponent of the variable x that results from multiplying the factors of f(x) is 4